(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Surgical site infection (SSI) is one of the most common postoperative complications. The prevalence of antibiotic-resistant pathogens causing SSI has been increasing, particularly multidrug-resistant strains such as methicillin-resistant Staphylococcus aureus (MRSA) and Klebsiella pneumoniae. Objective: To investigate the prevalence of SSIs, microbiological characteristics, and antibiotic resistance patterns in patients undergoing neurosurgery. Methods: A cross-sectional descriptive study was conducted using retrospective medical record data. Results: Among 257 medical records reviewed, 68.1% were male patients. The mean age was 46.5 ± 17.1 years. Comorbidities were present in 45.5% of patients, of whom 8.2% had diabetes mellitus. All patients underwent open surgery. The incidence of SSI was 5.1%, with superficial SSIs accounting for 3.5%. Causative pathogens included Gram-negative bacteria (30.8%, mainly Klebsiella) and Gram-positive bacteria (69.2%, mainly S. aureus). Conclusion: The incidence of SSI was 5.1%, predominantly superficial infections. The main causative agents were Klebsiella and S. aureus. Enhanced microbiological surveillance and rational antibiotic use are essential to control SSIs and limit antimicrobial resistance.